Simultaneous Determination of Six Components in Jingzhiguanxin Tablet by High-Performance Liquid Chromatography - Jiang, Hui; Fu, Lianhao; Wang, Yu; Wang, Shaozhi; Zhang, Xiaoxu; Zhang, Xijie; Liu, Xiaohong (Current Pharmaceutical Analysis, 2019)
Background: Jingzhiguanxin (JZGX) tablet, a traditional Chinese prescription, is commonly used for treating coronary heart disease and angina pectoris in the clinic. There are six active components (Danshensu (DSS), Protocatechuic aldehyde (PD), Paeoniflorin (PF), Ferulic acid (FA), Salvianolic acid B (Sal B) and Tanshinone IIA (TA)) in JZGX tablet. Objective: In this paper, a simple and reliable method was used for simultaneous determining the six active components by high-performance liquid chromatography coupled with diode array detector (HPLC-DAD). Methods: These six active components were separated on an Agilent Zorbax Eclipse XDB-C18 column (150 mmx4.6 mm, 5 μm) at 30 °C. Acetonitrile (A), methanol (B) and 0.5% H3PO4 aqueous solution (C) were used as mobile phase for gradient elution. The flow rate was 1 mL/min and the detection wavelengths were set at 280 nm for DSS, PD and Sal B, 230 nm for PF, 320 nm for FA and 270 nm for TA, respectively. Results: All of the six components showed good linearity regressions (r2≥0.9997) in the detected concentration range. The recovery rates and coefficient of variation (CV) for all analytes were 98.66%- 100.18% and 0.75%-1.89%, respectively. This method was successfully applied to simultaneously determine the six components in JZGX tablet from different batches and manufacturers. Conclusion: The validated method can be used in routine quality control analysis of JZGX tablet without any interference.
Keywords: Diode Array Detection (DAD)